2018
DOI: 10.1108/jmp-11-2017-0402
|View full text |Cite
|
Sign up to set email alerts
|

Predicting career success: is the dark side of personality worth considering?

Abstract: Purpose-The purpose of this paper is to clarify whether the dark side of personality adds information beyond the bright side when predicting career success. Design/methodology/approach-In total, 287 participants (150♀, M age ¼ 37.74 and SD age ¼ 10.38) completed questionnaires on the Dark Triad (narcissism, Machiavellianism and psychopathy) and the Big Five (emotional stability, extraversion, openness, agreeableness and conscientiousness). They also provided information on their objective (salary and leadershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 78 publications
3
17
0
1
Order By: Relevance
“…Career success reflects the accumulation of an individual's achievements as a result of their work experience and has intrinsic and extrinsic components (Judge et al, 1995). Grandiose narcissism has been found to be positively related to income in some studies (Paleczek et al, 2018;Spurk et al, 2016) but not in others (Hirschi & Jaensch, 2015), a difference that may arise from the use of convenience samples (Hirschi & Jaensch, 2015;Spurk et al, 2016). Furthermore, distinguishing between adaptive and maladaptive dimensions of grandiose narcissism may also explain the different findings (Leckelt et al, 2019).…”
Section: Narcissism and Incomementioning
confidence: 99%
See 1 more Smart Citation
“…Career success reflects the accumulation of an individual's achievements as a result of their work experience and has intrinsic and extrinsic components (Judge et al, 1995). Grandiose narcissism has been found to be positively related to income in some studies (Paleczek et al, 2018;Spurk et al, 2016) but not in others (Hirschi & Jaensch, 2015), a difference that may arise from the use of convenience samples (Hirschi & Jaensch, 2015;Spurk et al, 2016). Furthermore, distinguishing between adaptive and maladaptive dimensions of grandiose narcissism may also explain the different findings (Leckelt et al, 2019).…”
Section: Narcissism and Incomementioning
confidence: 99%
“…There might be two major reasons for the contrast between our results and previous findings. First, previous studies (Hirschi & Jaensch, 2015;Paleczek et al, 2018) used either the NPI (Raskin & Hall, 1979) or the Dirty Dozen (Spurk et al, 2016), neither of which differentiate between the dimensions of narcissism and both of which contain somewhat "weaker" statements than the NARQ. Therefore, more people should be likely to choose higher ratings, thus leading to more variance in the narcissism variable.…”
Section: Implications Of the Associations Of Admiration Rivalry And Incomementioning
confidence: 99%
“…Even though it is not without limitations, it is the most widely accepted taxonomy and builds on a vast number of empirical studies demonstrating its reliabilities and validities in diverse fields, including entrepreneurship (Şahin et al, 2019). Due to the Five-Factor Model's status as the "scientific standard" (Paleczek et al, 2018) we apply it in this study.…”
Section: Personality Traits and Entrepreneurial Intentionmentioning
confidence: 99%
“…Similarly, leaders’ traits have been shown to predict their self‐reported behavior, and their traits have been shown to predict followers' ratings of the leaders' behavior; however, those two effects do not always align (Colbert et al, 2012; de Vries, 2012: McKee et al, 2018). For example, Hautala (2006) found that leaders’ extraversion predicted their self‐reported leadership, while Paleczek et al (2018) found that leaders' sensing preferences (and not extraversion) predicted followers' ratings of leadership. In contrast, Brandt and Laiho (2013) found that the same leader trait predicted both self‐reported and follower‐rated behavior.…”
Section: Literature Reviewmentioning
confidence: 99%